Asuransi Tanggung Gugat Kapal Terhadap Risiko dan Evenemen Dalam Kegiatan Pelayaran Perdagangan Melalui Jalur Laut - Rani, Marnia (Jurnal Selat, 2016)
The most of the worldâs trade is carried by sea.  There is always a risk that the object of the trade  may be delayed, damaged or lost in transit.Many events can occur during transit. For example, traders may be involved in an accident whereby the goods are destroyed or might be stolen.The result can be loss of profits.  Traders should therefore insure their goods against loss, damage or delay in transit to minimize the impact of such incidents on their business by being properly insured. One of mechanism by cover the risk of loss or damage the goods with marine insurance. This can cover the whole journey-over land as well as sea. Basically, marine insurance is third party vesselinsurance. This insurance covers liability for loss or damage to someone elseâs property, arising from operation of the vessel. Third party vessel insurance, more commonly knowns as legal liability insurance (Protection and Indemnity insurance).There are many insurable interest can be covers by marine insurance, especially on legal liability insurance. The insurable interest in marine insurance like liability in respect of passanger, cargo liability, liability in respect of the crew members, ship collision, sea pollution risk, towage liabilities, liability for obstruction and wreck removal, and liability of damage to property port and navigation tools/telecommunications cruise. The problem in this research is the importance of legal liability insurance for the transfer of risk if loss or damage may be happen to the third party, arising from operation of the vessel.The second problem is about regulation on marine insurance in Indonesia.This research classified by normative legal research with descriptive type of explanatory and analytical approach to normative legal substance (approach of legal content analisys).The outcome of the research shows that the legal liability insurance has an important role for protecting the third parties for loss or damage, arising from operation of the vessel at sea. The second problem in this research is the regulation regarding marine insurance in Indonesia. Marine Insurance Regulation in Indonesia is Commercial Code since 1847 which is regulated colonial legacy from Deutch, had been outstanding for more than 150 years. While the development of todays insurance business has been growing very rapidly.It is necessary to create regulations governing marine insurance. Keywords: Marine Insurance, Legal Liability Insurance.